Intervención del terapista respiratoria en paciente neonato pretérmino con membrana hialina. - Engracia Álava, Jomira Sisney (2023)
In this undergraduate project, he focused on investigating the effects of continuous positive airway pressure (CPAP) in a neonatal patient with hyaline membrane disease (HMD), with the aim of demonstrating the benefit of continuous positive airway pressure support in the post extubation airway in alveolar ventilation in the preterm neonate with hyaline membrane disease. To evaluate respiratory distress in a preterm neonate with hyaline membrane disease. Within the follow-up data, it was found that the main risk of preterm birth was associated with lung immaturity and cytological defects. Surfactant deficiency due to prematurity causes atelectasis with diffuse alveolar networks, the severity of which varies with the level of phospholipids. A 1-hour-old preterm neonate of 36 weeks gestation with an Apgar score of 7-8 at birth with a weight of (2200 g) and a temperature of 36.5°C was treated and noted respiratory failure, cyanosis , intercostal and subcostal retractions, expiratory grunting, nasal flaring and impaired respiratory ventilation with a saturation of 84%. He was initially treated with high-flow oxygen therapy, the clinical picture evolved, therefore, it was decided to intubate and place phospholipid. And one of the non-invasive ventilatory support measures to prevent alveolar collapse was the use of continuous positive airway pressure (CPAP), obtaining excellent results for hyaline membranes, resolving most cases and being useful in a minority of cases, providing significant opportunities and advances in the non-invasive ventilation experience.